Bone Grafting Recent Advances with Special References to Cranio-Maxillofacial Surgery - Kummoona, Raja (IntechOpen, 2018)
This valuable book presents clinical experiences and research of bone grafting. Bone grafting is an essential technique practiced by craniofacial, maxillofacial, orthopedic, neuro, reconstructive and oral surgeons. Bone grafting can be used for reconstruction and restoring missing bone in trauma and tumor surgery of the facial bone or in road traffic accidents with multiple injuries and in post-traumatic missile war injuries to the face or limbs. Bone grafts, in the form of Kummoona Chondro-Ossous graft or Costo-Chondral graft, are used for reconstruction of damage TMJ for restoration of growth, function, and repair. Bone grafting is a surgical procedure where the iliac crest or rib or tibia is used to perform grafting. In this book, we examine the experimental studies on rabbits to understand the cellular changes associated with bone grafting. From this, we noticed that mesenchymal stem cells and growth factor are released from platelets and these play an important role in healing the bone graft. We recommend this valuable book to all cranio-maxillofacial, orthopedic, plastic, reconstructive, neuro and oral surgeons and to all postgraduate students studying bone grafting.